Korean species of the Atheta Thomson subgenus Dimetrota Mulsant & Rey (Coleoptera: Staphylinidae: Aleocharinae) with a description of new species - Lee, Seung-Gyu; Ahn, Kee-Jeong (Zootaxa, 2022)
A taxonomic review of the Atheta Thomson subgenus Dimetrota Mulsant & Rey in the Korean Peninsula is presented. The subgenus is represented in Korea by 11 species including a new species, A. (D.) ovata Lee & Ahn, sp. nov. and a new synonym [A. (Badura) tokiokai Sawada = A. (D.) chagangensis Paśnik syn. nov.]. Atheta (D.) yamamotoi Sawada is reported for the first time in the Korean Peninsula and A. (D.) machonryongica in South Korea. A key to Korean species and descriptions with illustrations of habitus photographs and diagnostic characters of three species new to Korea are provided.